EFFORTS TO REDUCE THE BEHAVIOR OF BEING LATE TO LECTURES FOR STUDENTS AT MUHAMMADIYAH UNIVERSITY OF NORTH SUMATRA - Satria, Bagas; Sinulingga, Rajesta; Simamora, Bangun; Hirzi, Nadhil; Mavianti, Mavianti (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to find out the efforts to reduce the behavior of being late for lectures on students at the Muhammadiyah University of North Sumatra. The method used in this research is a qualitative method. Data collection techniques used are descriptive, interviews, documentation. The data analysis technique used in this study is to use the Miles Huberman model analysis technique, namely in conducting data analysis there are four stages: data collection, data reduction, data presentation, conclusion and verification. The data validity guarantee technique in this study is to use triangulation. The results of this study are that there are two factors that cause students to be late, namely internal factors and external factors. And being late is divided into two types, namely intentional late and unintentional late. Efforts made to reduce late behavior in students are motivation, family, and lecturer guidance.